Utilization of plant-based protein-polyphenol complexes to form and stabilize emulsions: Pea proteins and grape seed proanthocyanidins. (1st November 2020) - Dai, Taotao; Li, Ti; Li, Ruyi; Zhou, Hualu; Liu, Chengmei; Chen, Jun; McClements, David Julian
Highlights: Pea protein (PP)–proanthocyanidin (GSP) complexes were formed and characterized. Isothermal titration calorimetry (ITC) was used to characterize PP-GSP interactions. Molecular simulations were used to elucidate PP-GSP interaction mechanisms. PP-GSP complexes were mainly held together by hydrogen bonding. PP-GSP complexes improved the stability of oil-in-water emulsions. Abstract: Plant-based proteins and polyphenols are increasingly being explored as functional food ingredients. Colloidal complexes were prepared from pea protein (PP) and grape seed proanthocyanidin (GSP) and the ability of the PP/GSP complexes to form and stabilize oil-in-water emulsions were investigated. The main interactions between PP and GSP were hydrogen bonding. The stability of PP-GSP complexes to environmental changes were studied: pH (2–9); ion strength (0–0.3 M); and temperature (30–90 °C). Emulsions produced using PP-GSP complexes as emulsifiers had small mean droplet diameters (~200 nm) and strongly negative surface potentials (~−60 mV). Compared to PP alone, PP-GSP complexes slightly decreased the isoelectric point, thermostability, and salt stability of the emulsions, but increased their storage stability. The presence of GSP gave the emulsions a strong salmon (red-yellow) color, which may be beneficial for some specific applications. These results may assist in the creation of more efficacious food-based strategies for delivering proanthocyanidins.